Mecanismos de ação espasmolítica da caulerpina, alcaloide bisindólico isolado de algas marinhas do gênero Caulerpa, em íleo de cobaia - Silva, Luiz Henrique Agra Cavalcante (2013)
Caulerpine (5,12-dihydro-cycloocta[1,2-b;5,6-b']diindole-6,13-dicarboxylic acid dimethyl ester) is a bisindole alkaloid which are isolated from ethyl acetate phase from marine algae Caulerpa mexicana and C. sertularioides. Since that other indole alkaloids have been shown spasmolytic activity on intestinal smooth muscle, we aimed to investigate a possible spasmolytic activity of caulerpine on guinea pig ileum. Caulerpine (3 x 10-6 – 3 x 10-4 M) antagonized phasic contractions in a significant and equipotent manner induced by 10-6 M carbachol (IC50 = 7.0 ± 1.9 x 10-5 M, Emax = 62.0 ± 7.6%), 10-6 M histamine (IC50 = 1.3 ± 0.3 x 10-4 M, Emax = 71.0 ± 4.9%) or 10-5 M serotonine (IC50 = 8.0 ± 1.4 x 10-5 M, Emax = 73.8 ± 1.4%), proving a non-selective spasmolytic effect on guinea pig ileum. Furthermore, caulerpine inhibited cumulative concentration-response curves to serotonin, and these were shifted to the right, in a non-parallel manner, with Emax reduction, discarding thus a competitive type antagonism (slope = 2.44 ± 0.21). The adrenergic receptors involvement, relevant in many functions of gastrointestinal tract, also was carried out. It was observed that 2 adrenergic receptors are not involved in spasmolytic effect of caulerpine, since caulerpine-induced relaxation curve (EC50 = 4.7 ± 0.7 x 10-5 M) was not shifted in the presence of 1.3 μM yohimbine (EC50 = 5.7 ± 0.7 x 10-5 M), an antagonist of these receptors. However, this was not observed in presence of propranolol, an antagonist of β adrenergic receptors, where caulerpine-induced relaxation curve was shifted five folds in the presence of 5 μM propranolol (EC50 = 2.2 ± 0.2 x 10-4 M), suggesting the participation of β adrenergic receptors on spasmolytic effect of caulerpine. Caulerpine also relaxed the ileum pre-contracted with 40 mM KCl (EC50 = 9.1 ± 0.9 x 10-5 M, Emax = 94.8 ± 2.6%), indicating that caulerpine could be acting voltage-gated Ca2+ channels (CaV). This hypothesis was confirmed since caulerpine inhibited CaCl2-induced contractions in the depolarizing (70 mM KCl) medium nominally without Ca2+. The fact that caulerpine until 3 x 10-4M did not inhibit phasic contractions induced by 10-6 M carbachol on circular layer from guinea pig ileum corroborates the hypothesis that it inhibits the influx of Ca2+ through CaV. Thus, it was investigated if this blocked was happened in an indirect manner by K+ channels opening. However, the findings showed that caulerpine-induced relaxation curve (EC50 = 4.7 ± 0.7 x 10-5 M) was not shifted in the presence of 5 mM CsCl (EC50 = 3.0 ± 0.7 x 10-5 M), a non-selective K+ channels blocker, indicating that K+ channels are not involved on spasmolytic effect of caulerpine. Taken together, these results suggest that caulerpine shows a non-selective spasmolytic effect and one of the possible mechanisms involved in this activity is blockade of Ca2+ influx through CaV blockade and activation of β adrenergic receptors.